Integrasi Media Visual Motif Batik dalam Pembelajaran BIPA untuk Meningkatkan Kosakata Budaya dan Pemahaman Simbolik - Siti Yatimah; Resdiantoraharjo Resdiantoraharjo (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to analyze the integration of visual media in the form of batik motif images in Indonesian for Foreign Speakers (BIPA) learning and to examine its contribution to the acquisition of cultural vocabulary and the understanding of symbolic meanings. BIPA learning requires the integration of linguistic and cultural aspects to enable learners to communicate appropriately in social contexts. However, cultural instruction in practice is still largely dominated by verbal approaches that provide limited contextual learning experiences. Therefore, the use of visual media is considered a promising alternative to enhance the quality of instruction.This study employs a descriptive qualitative approach involving beginner-level BIPA learners as the research subjects. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques.The findings reveal that the use of visual media featuring batik motifs has a positive impact on the learning process. Learners demonstrate higher levels of participation, improved acquisition of culture-related vocabulary, and a deeper understanding of the philosophical values embedded in batik motifs. The visualization of patterns, colors, and designs enables learners to build more concrete meaning associations compared to relying solely on textual explanations.These findings indicate that the integration of visual literacy in culture-based BIPA learning plays a significant role in enhancing learners’ communicative competence. Furthermore, this study offers practical contributions in the form of an implementative model for utilizing local culture-based visual mediamedia that enables adapted in the development of BIPA instructional materials and curriculum development.